Impact of Fitspiration Content on Social Media among Followers in Singapore Universities - Poh, Jia Hui Shericia; Chung, Ho Jin (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2021)
Fitspiration content on social media has been popularized over the last few years, with the intention to influence users to lead healthy and fit lifestyles. The present study aimed to identify the impact of fitspiration content on social media among young adult followers in Singapore. Method: Participants were 124 university students in Singapore who completed a cross-sectional survey. The survey included 16 multiple choice questions, 4 short-answer questions and 8 open-ended questions. Descriptive statistics was adopted for quantitative data and content analysis was utilized for qualitative data. The perceived impact of fitspiration content was explained through three themes: 1) Positive impact of fitspiration content on social media, 2) Negative impact of fitspiration content on social media, and 3) Perceived impact of social media on self. Three other themes were also developed for understanding the conditions influenced by fitspiration content on social media: 1) Evaluation and satisfaction with one’s fitness journey, 2) Motivational levels of participants, and 3) Diet restrictions. Results showed that positive impact were experienced by the majority of the participants, whereas some participants experienced negative impacts. It was concluded that fitspiration content on social media does inspire users to become a better version of themselves both physically and mentally. However, it is also dependent on the perceptions of the users and the extent to which they allowed such content to influence them.